2011
DOI: 10.1016/j.ypmed.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trends in gasoline price and physical activity: The CARDIA study

Abstract: Objective To investigate longitudinal associations between community-level gasoline price and physical activity (PA). Method In the Coronary Artery Risk Development in Young Adults study, 5,115 black and white participants aged 18–30 at baseline 1985–86 were recruited from four U.S. cities (Birmingham, Chicago, Minneapolis and Oakland) and followed over time. We used data from 3 follow-up exams: 1992–93, 1995–96, and 2000–01, when the participants were located across 48 states. From questionnaire data, a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
2
21
1
1
Order By: Relevance
“…Results in this study are consistent with Graham et al (2010), which provides a look at contemporary gasoline prices, but stand in contrast to the body of evidence that rising gasoline prices render contemporaneous improvements in physical health and health behaviors (Courtemanche, 2011;Hou et al, 2011;Rashad et al, 2005;Sen, 2011). Indeed, whereas this study finds that increasing prices lead to immediate reductions in subjective well-being, the extant literature generally concludes that obesity and overweight rates tend to fall and lifestyles become healthier as gasoline prices rise.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Results in this study are consistent with Graham et al (2010), which provides a look at contemporary gasoline prices, but stand in contrast to the body of evidence that rising gasoline prices render contemporaneous improvements in physical health and health behaviors (Courtemanche, 2011;Hou et al, 2011;Rashad et al, 2005;Sen, 2011). Indeed, whereas this study finds that increasing prices lead to immediate reductions in subjective well-being, the extant literature generally concludes that obesity and overweight rates tend to fall and lifestyles become healthier as gasoline prices rise.…”
Section: Resultssupporting
confidence: 87%
“…A final strand of research attempts to understand the mechanisms through which gasoline prices reduce obesity. Much of this work focuses on changes to health-related behaviors, including food consumption (Courtemanche, 2011) and physical activity (Courtemanche, 2011;Hou et al, 2011;Sen, 2011) patterns. These papers find that higher gasoline prices reduce the frequency of eating at restaurants while increasing the amount of physical activity from walking, housework, and yard work.…”
Section: Introductionmentioning
confidence: 99%
“…7% and obesity by approx. 10%.8Rabin et al 2007 [58]24 European countriesTo describe obesity patterns and examine macro-environmental factors associated with obesity prevalence.Ecological, cross-sectionalFuel price(Prevalence of obesity using BMI (S))The price of fuel was associated with obesity prevalence for females (b = −0.096, p -value 0.041) and overall (b = −0.095, p -value 0.0542), but not for men.5Sun et al 2015 [59]47 low-middle income countriesTo identify CVD risk factors in low-middle income countries.Ecological, cross-sectionalFuel price(Prevalence of obesity using BMI (S))The price of fuel was not statistically significantly associated with obesity in either men or women.5 Physical activity Hou et al 2011 [60]Birmingham, Chicago, Minneapolis and Oakland, USA. Young adults 18–30 years at baseline ( n  = 5115)To investigate longitudinal associations between fuel price and physical activity.Longitudinal cohortFuel price (Leisure PA - energy units (S))A hypothetical USD0.25 increase in fuel price significantly associated with increase in energy expenditure (9.9 energy units (EU), 95% UI: 0.8–19.1, p -value 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…For example, national level data show that the ownership of even one car dramatically transforms travel behavior: households with no vehicle take 41% of trips by walking compared with 12.5% trips by walking for households with one vehicle (Pucher & Renne, 2003). In a study (Hou et al, 2011) based on longitudinal data covering participants from 48 US states, $0.25 per gallon increase was found to be associated with 17 min of additional walking each week. Another study based on Behavioral Risk Factor Surveillance System (BRFSS) data between 1984 and 2006 found that, in urban areas, a person walks 0.5 times more per week when the price of gas rises by $1 per gallon (Courtemanche, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of work on transportation prices has focused on how it can reduce auto use or increase transit use (Guo, 2013; Marsden, 2006; Salon et al, 2012). Despite the importance of prices for people’s travel choices, there is limited research examining how pricing automobile use can also have an impact on walking behaviors (Courtemanche, 2011; Hou et al, 2011). For example, one recent review (Martin, Suhrcke, & Ogilvie, 2012) claimed that financial incentives may have a larger role in promoting walking and cycling than is acknowledged generally although the conclusion was based on evidence predominantly involving free bicycles or local road pricing at specific locations and for specific groups.…”
Section: Introductionmentioning
confidence: 99%